U. S. bases : adding the costs (Quezon City GMA Radio Television News and Public Affairs)
Discusses the security risks and the legal, economic and social problems involved in keeping the U. S. military bases in the Philippines.
Host, Jose Mari Velez.
Keywords: Military bases, American -- Philippines